Quality of medicines for Cardio-Vascular Diseases (CVDs) in the Ethiopian border with Kenya: The case of enalapril maleate and furosemide tablet quality in Borena and Gedeo zones. - Esayas Tesfaye; Fisseha Woldegiorgis; Tadele Eticha; Ayenew Ashenef (Public Library of Science (PLoS), 2024)
Hypertension (HTN), a cardiovascular disease (CV), is a major public health challenge. Therefore, the quality of drugs used to treat it has become a major concern. Enalapril and furosemide are among the drugs prescribed to manage hypertension. Hence, this study is aimed at evaluating the quality of different brands of enalapril and furosemide tablets available in the Gedeo and Borena zones, southern Ethiopia. Thirteen generic brands of enalapril maleate (5 mg) and furosemide (40 mg) tablets were evaluated for visual defects, in vitro dissolution test, weight variations, friability, hardness, and disintegration tests. The analysis of active pharmaceutical ingredient (API) content was performed by high performance liquid chromatography (HPLC). Out of 55 samples, 7 (12.73%) failed to comply with the criteria for visual inspection; otherwise, all samples passed the identification test. Except for one brand of each of enalapril maleate and furosemide, all passed the dissolution test. The assay value showed that all enalapril maleate samples were within the limits of United States Pharmacopoeia (USP), 2020. Additionally, except for two batches, all furosemide samples were within the USP and British Pharmacopoeia (BP), 2020 standards. Out of 55 samples, 8% (2/25) and 6.67% (2/30) of enalapril maleate and furosemide tablets failed the uniformity of dosage units test per the USP-2020, respectively. All samples passed the disintegration test, and selected furosemide samples passed the microbial limit tests. However, 36% (9/25) and 20% (6/30) of enalapril maleate and furosemide samples failed to pass hardness test. Generally, from the total samples, 50.91% (28/55) were substandard (did not meet the specifications failing any one or more parameters assessed). The studied drugs circulating in the market did not meet some of the needed quality specifications. This could have brought a risk of reduced efficacy due to the distribution of poor quality medicines in the area.